HIGH-DOSE I-131 THERAPY FOR VARIED ASPECTS OF WELL-DIFFERENTIATED THYROID CARCINOMA - THIENTUNYAKIT, Tanyaluck; PREMPRAPHA, Teerapon; THONGMAK, Suchitra (The ASEAN Journal of Radiology, 2023)
Purpose: This study aimed to evaluate the response to high-dose RAI (100-200 mCi) in three groups of patients: with a thyroid remnant, high Tg/negative WBS, and with metastasis. Materials and methods: We retrospectively chart-reviewed 159 patients who had been admitted and received high-dose RAI from October 1999 until August 2004 at our tertiary treatment center in southern Thailand. The indications for treatment included 1) a thyroid remnant after at least 2 OPD ablative doses, 2) high serum Tg with negative diagnostic WBS, and 3) I-131 avid metastasis. Results: 45 of 79 patients receiving high-dose I-131 for thyroid remnant ablation were successfully ablated. 12 of 24 patients with high Tg/negative WBS showed I-131 uptake on post-therapy WBS, while 3 showed no uptake on subsequent WBS; none returned to a normalized Tg level. Of 54 patients who had I-131 uptake in their metastases, 24 achieved complete response. There was no statistical difference in age, sex, histologic type, pre-treatment Tg level or accumulated small dose RAI between good and poor response groups. Conclusions: 1) A thyroid remnant (after surgery and small dose RAJ) could not be ablated with up to 250 mCi in 34/79 patients (43%). 2) In high Tg/negative WBS, high-dose RAI might improve sensitivity but without obvious benefit in therapeutic outcome. 3) 24 out of 54 metastases (44%) showed a positive response to high-dose RAI, particularly those exhibiting RAI uptake at a single site WBS = Whole body Scan